IMPROVING LEARNING OUTCOMES OF SHOOTING SOCCER WITH AUDIO VISUAL MEDIA IN CLASS V STUDENTS OF SD TITI BERDIKARI MEDAN - Lubis, Ade Evriansyah; Agung Nugroho (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna Medan, 2020)
This study aims to determine the increase in learning outcomes in soccer shooting in the fifth grade students of SD Titi Berdikari Medan in the Academic Year 2018/2019, through Audio Visual Media. This research is a Classroom Action Research (CAR). The study was conducted in two cycles, with each cycle consisting of planning, action, assessment, and reflection. The data source in this study was in the form of a test to students in the form of the application of the basic technique of shooting soccer. The technique of data collection is done by evaluating the results of learning to shoot soccer. The data analysis technique used is descriptive based on a qualitative analysis with a percentage. The results obtained from the observation that 15 students were declared complete (47%) while 17 other students were declared incomplete (53%). In the first cycle the results obtained where 24 students declared complete (75%) while 8 other students declared incomplete (25%). And in the second cycle the results obtained were 27 students declared complete (85%) while 5 other students were declared incomplete (15%).